HUBUNGAN ANTARA KEMATANGAN EMOSI DENGAN PENGAMBILAN KEPUTUSAN STUDI LANJUT SISWA KELAS IX SMP NEGERI SE-KECAMATAN MUARA BANGKAHULU - Roina Venecia Br. Batu Bara; Rita Sinthia; Arsyadani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
This research aimed to describe the relationship between emotional maturity and decision making for further studies in class IX students in Muara Bangkahulu sub-district. This research uses quantitative methods. The population in the study were all class IX students in the Muara Bangkahulu sub-district, totaling 497 students with the research sample used totaling 149 students which is 30% of the total population using random sampling techniques. The data collection techniques used in this research were emotional maturity questionnaire instruments and further study decision making questionnaires using the Likert scale model. In testing the relationship between emotional maturity and decision making for further studies using hypothesis testing, where the results of hypothesis testing there is a correlation of 0.590 with a significance value of 0.000. Ho is rejected and Ha is accepted, which means there is a significant relationship between emotional maturity and decision making for further studies in class IX students. Muara Bangkahulu sub-district. Keywords: emotional maturity, decision making, further study, students